The effects of saccharin and sodium dodecyl sulfate on hardness of nickel electrochemically deposited in submillimeter scale trench patterns - Razmi Hariz Bin Rahmat (2014)
The effects of PEG, saccharin and sodium dodecyl sulphate (SDS) additives on the electrodeposition of nickel are investigated. The aim of the project is to improve hardness property of the nickel plated and maintain bottom-up deposition, by ensuring additives does not affect the inhibitive effects of PEG. The improvements to the hardness of the nickel filling are studied by measuring the micro hardness through a Vickers’s hardness test. The experimental results show that with addition of additives, there is an improvement in hardness. However, only saccharin can be considered for future testing as SDS removes PEG’s inhibitive effect. Optimal hardness is achieved at saccharin 2857.14 ppm. Any amount above this level will decrease the hardness of nickel filling. Other tests were done to further improve the electro-deposition process.